Hereditary Colorectal Cancer Genetic Basis and Clinical Implications (Springer International Publishing, 2018)
This book provides information on a wide variety of issues ranging from genetics to clinical description of the syndromes, genetic testing and counseling, and clinical management including surveillance, surgical and prophylactic interventions, and chemoprevention. Moreover, current hot issues, such as the identification of novel causal genes and the challenges we face, and the relevance of cancer risk modifiers, both genetic and environmental, are also discussed. This reference book is great for geneticists, oncologists, genetic counselors, researchers, clinicians, surgeons and nurses dedicated to, or interested in, hereditary cancer. The best and most recognized experts in the field have contributed to this project, guaranteeing updated information, accuracy and the discussion of topical issues.